2013
DOI: 10.1177/1461444813495159
|View full text |Cite
|
Sign up to set email alerts
|

Do online communication attitudes mitigate the association between Facebook use and relational interdependence? An extension of media multiplexity theory

Abstract: Given Facebook's popularity for the maintenance of interpersonal relationships, this investigation examined the extent to which frequency of Facebook communication with a specific friend predicts relational interdependence. The chief goal of the investigation was to extend media multiplexity theory by examining whether attitudes toward (a) online self-disclosure and (b) online social connection moderated this association. Results not only replicated previous findings that multiple media are associated with rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 43 publications
(107 reference statements)
3
38
0
Order By: Relevance
“…Online daters who contacted each other using a greater variety of channels prior to meeting F2F reported that their relationship was more intimate (Ramirez, Sumner, Fleuriet, & Cole, 2015). Other studies have reported positive associations between relational development and multiplex media use, as well as modest but significant differences in particular combination of media used depending on type of relationship and participants' attitudes toward the role of online communication in personal relationships (Ledbetter, 2014;Ledbetter & Mazer, 2014).…”
Section: Media Multiplexitymentioning
confidence: 99%
See 1 more Smart Citation
“…Online daters who contacted each other using a greater variety of channels prior to meeting F2F reported that their relationship was more intimate (Ramirez, Sumner, Fleuriet, & Cole, 2015). Other studies have reported positive associations between relational development and multiplex media use, as well as modest but significant differences in particular combination of media used depending on type of relationship and participants' attitudes toward the role of online communication in personal relationships (Ledbetter, 2014;Ledbetter & Mazer, 2014).…”
Section: Media Multiplexitymentioning
confidence: 99%
“…People not only use the telephone to connect with others and obtain social support in times of crisis, but also reach out to others using the Internet (Dutta-Bergman, 2004b). In personal relationships more generally, the frequencies of instant messaging, e-mail, texting, Facebook posting, and telephone calls are positively related (e.g., Ledbetter, 2014;Ledbetter & Mazer, 2014;Ramirez & Broneck, 2009).…”
Section: Theoretic Precursors To the Study Of Mixed-media Relationshipsmentioning
confidence: 99%
“…Given the fact that almost every participant reported a close relationship with one or both of their parents, this finding suggests that contextual factors such as pace of life and intergenerational differences affect the association between relational tie strength and number of technologies used. In line with Ledbetter and Mazer's (2014) research on attitudes and media choice, the strength of the association is reduced by the limited number of media toward which both parties À here college students and their parents À have mutually strong positive attitudes. Furthermore, students' attitudes were significantly influenced by how well they felt the technology fit into their busy lives.…”
Section: Discussionmentioning
confidence: 84%
“…Ledbetter and Mazer's (2014) extension of media multiplexity theory suggests that attitudes toward communication technologies influence choice of media in the absence of explicit group or institutional norms, and that strong tie relationships will "employ communication media about which they hold the mutually strongest positive attitudes" (p. 13). Ledbetter and Mazer also call for further research on contexts in which relational partners are likely to differ in their preferred mediums for communication.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Analysis of the Internet influence on political activity of the Dutch is devoted work of Kruikemeier, Noort, Vliegenthart and Vreese (2014), (see. Also Tufekci andWilson 2012, Ledbetter andMazer 2014 andmany others). This classification is different from the classification shown in Bober, M. and Helsper, E. (2004), which, in particular, can be explained by the specificity of the Russian society.…”
Section: Name Of the Social Network The Monthly Audience (Person) Actmentioning
confidence: 99%